Cloning, overexpression and biocatalytic exploration of a novel Baeyer-Villiger monooxygenase from Aspergillus fumigatus Af293 - Mascotti, María Laura (2013)
The presence of several putative Baeyer-Villiger Monooxygenases (BVMOs) encoding genes in Aspergillus fumigatus Af293 was demonstrated for the first time. One of the identified BVMO-encoding genes was cloned and successfully overexpressed fused to the cofactor regenerating enzyme phosphite dehydrogenase (PTDH). The enzyme named BVMOAf1 was extensively characterized in terms of its substrate scope and essential kinetic features. It showed high chemo-, regio- and stereoselectivity not only in the oxidation of asymmetric sulfides, (S)-sulfoxides were obtained with 99% ee, but also in the kinetic resolution of bicyclo[3.2.0]hept-2-en-6-one. This kinetic resolution process led to the production of (1S,5R) normal lactone and (1R,5S) abnormal lactone with a regioisomeric ratio of 1:1 and 99% ee each. Besides, different reaction conditions, such as pH, temperature and the presence of organic solvents, have been tested, revealing that BVMOAf1 is a relatively robust biocatalyst.